2016
DOI: 10.1103/physreve.94.022803
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic attraction between overall neutral surfaces

Abstract: Two overall neutral surfaces with positive and negative charged domains ("patches") have been shown in recent experiments to exhibit long-range attraction when immersed in an ionic solution. Motivated by the experiments, we calculate analytically the osmotic pressure between such surfaces within the Poisson-Boltzmann framework, using a variational principle for the surface-averaged free energy. The electrostatic potential, calculated beyond the linear Debye-Hückel theory, yields an overall attraction at large … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
(111 reference statements)
0
15
0
Order By: Relevance
“…In recent years considerable theoretical interest has emerged in the effective interaction between two heterogeneously charged walls (which typically are the surfaces * Electronic address: mussotter@is.mpg.de † Electronic address: bier@is.mpg.de of colloidal particles) mediated by an electrolyte solution [16][17][18][19][20][21][22][23][24][25][26]. In contrast to uniform substrates, this effective interaction can lead to lateral forces, in addition to the common ones in normal direction.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years considerable theoretical interest has emerged in the effective interaction between two heterogeneously charged walls (which typically are the surfaces * Electronic address: mussotter@is.mpg.de † Electronic address: bier@is.mpg.de of colloidal particles) mediated by an electrolyte solution [16][17][18][19][20][21][22][23][24][25][26]. In contrast to uniform substrates, this effective interaction can lead to lateral forces, in addition to the common ones in normal direction.…”
Section: Introductionmentioning
confidence: 99%
“…The disorder in the surface charge can be quenched [2] or annealed [3]. While the interaction between surfaces in the annealed case mainly involves polarization effects somewhat similar to van der Waals interactions, the quenched case is very sensitive to counterion release [4]. Some theoretical efforts were devoted to quenched systems involving multivalent counterions [5] for which strong and unexpected effects were described [6].…”
mentioning
confidence: 99%
“…Furthermore, we lift the constraint of overall charge neutral walls, as has been used in Refs. [17,21,23,27]. The present study addresses the open questions from Ref.…”
Section: Introductionmentioning
confidence: 84%
“…Over the last years, an increasing interest in these surfaces has developed, leading to a number of studies investigating the influence of heterogeneously charged walls, for example on the effective interaction between two substrates in contact with an electrolyte solution [17][18][19][20][21][22][23][24][25][26][27]. These studies revealed the effective interaction in case of nonuniform substrates to cause lateral forces in addition to the ones in normal direction, which are commonly known.…”
Section: Introductionmentioning
confidence: 99%